2013
DOI: 10.1002/aenm.201300787
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Degradation Mechanisms of LiNi0.5Co0.2Mn0.3O2 Cathode Material in Lithium Ion Batteries

Abstract: Figure 4. HR-TEM images and FFTs after 50 cycles under 3.0-4.8 V conditions. a) Lattice image of the surface region where (b-e) correspond to the FFTs of Regions 1-4, respectively. (11-1) c is the diffraction spot of the rock salt phase of the metal monoxide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

30
767
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 967 publications
(801 citation statements)
references
References 35 publications
30
767
1
3
Order By: Relevance
“…Though no significant bulk structural change was observed from XRD, some structural changes may have occurred on the surface, which contribute to the irreversible capacity loss and impedance growth. 16,43 In particular, Ni 4+ is known to be highly reactive with the electrolyte, which leads to surface reconstruction and the buildup of surface reaction layers. In addition, formation and growth of cracks in the cathode particles degrade their ionic and electronic connectivity and further lead to a sluggish, incomplete reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Though no significant bulk structural change was observed from XRD, some structural changes may have occurred on the surface, which contribute to the irreversible capacity loss and impedance growth. 16,43 In particular, Ni 4+ is known to be highly reactive with the electrolyte, which leads to surface reconstruction and the buildup of surface reaction layers. In addition, formation and growth of cracks in the cathode particles degrade their ionic and electronic connectivity and further lead to a sluggish, incomplete reaction.…”
Section: Resultsmentioning
confidence: 99%
“…The passivation layer forms during the rst charge, 12 and during exposure to electrolytic solution, 10,12 and accumulates during extended charging-discharging cycles. 10,11 The passivation layer inhibits lithium diffusion kinetics and increases the overall cell impedance, leading to the loss of practical capacity at moderate discharge rates. However, it has been shown that the lost capacity can mostly be recovered when a much slower charging rate is adopted.…”
Section: 8mentioning
confidence: 99%
“…The reliability of NMC materials at high voltages is strongly governed by the structural and chemical stability at the particle surfaces. [10][11][12] The particle surfaces usually undergo undesirable structural and chemical evolution (surface passivation) under harsh cycling conditions, such as high-voltage cycling. One of the major passivation mechanisms is surface reconstruction through the reduction of transition metals to form rock-salt and/or spinel phases.…”
Section: 8mentioning
confidence: 99%
“…17 This leads to cell impedance rise and an effective loss of capacity. In addition, rock salt or mixed rock salt/spinel phases on particle surfaces have been detected under various cycling or storage conditions for NMC-442, 18 LiNi 0.5 Mn 0.3 Co 0.2 O 2 (NMC-532), 19 and LiNi 0.8 Mn 0.1 Co 0.1 O 2 (NMC-811). 20 In the study of NMC-532, it was found that surface reconstruction to a rock salt phase dominates when high voltage (4.8 V) cutoffs are used due to oxygen loss under the highly oxidizing conditions, while spinel forms under milder cycling conditions.…”
mentioning
confidence: 99%